(untitled) (Research, Society and Development, 2021)
The number of markets and street markets in the municipality of Belém/PA has been multiplying in an enhanced manner. These have very particular training and functioning dynamics, often presenting terrible working conditions with few or no hygiene and safety. The objective of the research was to identify risk agents in the activities developed by workers at the Ver-o-Peso Complex, Belém/PA, using the Preliminary Hazard Analysis technique. Bibliographic review and site visits were carried out during October 2020. In total, 27 potential hazards associated with different activities developed by workers were identified. These hazards are related to physical, chemical, biological, ergonomic and mechanical risk agents or accidents. The origin of the risks found comes from different elements of the work process, such as: materials, equipment, acoustic and thermal comfort, installations and lighting. The biological risk was the greatest risk potential for local workers. Physical and chemical risks and most ergonomic and mechanical agents or accidents have moderate risk potential. It revealed the need for investments by the government, aimed at training and qualifying local workers, in addition to improvements in the physical structure of the complex.